Religion and women - Sharma, Arvind (McGill studies in the history of religions., 1994)
This book discusses the position of women in the Native American, African, Shinto, Jaina, Zoroastrian, Sikh, and Baha'i faiths for the first time in a single volume, and evolves a conceptual framework within which their positions could be comprehensively considered. The contributing scholars provide an enlarged database for a more thorough discussion of the questions pertaining to women and religion in general, and simultaneously advance the theoretical frontiers in women's studies. Religion and Women belongs to a trilogy about women and world religions edited by Arvind Sharma the first and third volumes being respectively, Women in World Religions and Today's Woman in World Religions.